Increasing the Ability of Indonesian in Determining Story Elements by Applying Concept Mapping Methods Assisted by Graphic Media - Carsinem, Carsinem (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study is to improve Indonesian language skills in determining the elements of the story by applying the concept mapping method assisted by graphic media. The research conducted was a Classroom Action Research (CAR) in two cycles, with each cycle consisting of one meeting. In cycle I, the results of student activities through evaluation were obtained from all students as many as 35 students, there were 20 students completed and 15 students had not completed, with a persetanse of 57% and 43%. In the second cycle, it was decided that the students experienced an increase in completeness as expected. In cycle II, there were 29 students who had completed and 6 students who had not yet completed, with a percentage of 83% and 17%. The application of the Concept Mapping learning model can improve the learning outcomes of Class 4 students in Indonesian muples in determining the elements of the story. Students will always remember as provisions for the future in everyday life, students are able to determine the elements of the story correctly.